Massive pulmonary thromboembolism in a patient with Crohn's disease and latent tuberculosis treated with ustekinumab - Chávez-Sánchez, Siomara Aransuzú (2023)
Inflammatory bowel disease (IBD) is a spectrum of chronic immune-mediated diseases that affect the gastrointestinal tract and other extraintestinal systems, behaving as a systemic disease. Thromboembolic phenomena are a frequent complication in IBD, because of hypercoagulability states associated with disease activity, and their presence has a negative impact on prognosis and patient survival. Due to this, the control of the inflammatory activity of IBD is one of the pillars in the control of thromboembolic events. Biological drugs are associated with rapid control of the inflammatory process, however, the security profile for the reactivation of latent infections, particularly tuberculosis, is always discussed. We present the case of a 37-year-old patient who presented with deep vein thrombosis in the left lower limb and later with massive pulmonary thromboembolism. During his evaluation, he was diagnosed with Crohn's disease (CD). When carrying out the studies prior to the use of biologics, PPD and quantiferon tests were positive. After discussing the case, we decided to start treatment with ustekinumab.